Address and involvement in e-books about COVID-19 for young children: an analysis of the visual mode. Issue 2 (3rd April 2022) - Koutsikou, Maria; Christidou, Vasilia
Abstract: COVID-19 e-books have emerged as means for communicating information about coronavirus and the resulting disease to children during the pandemic. This material is multimodal, with images forming the most prevalent and crucial semiotic mode. Except for representational and compositional meaning, an image realises interpersonal meanings. The degree to which the reader is activated (address) and prompted to become engaged with what is represented (involvement) constitute interpersonal meaning dimensions that reflect crucial pedagogical perceptions about children's learning. This study explored how address and involvement are visually realised in young children's e-books about COVID-19. The sample consisted of 100 randomly selected images of living or anthropomorphic entities included in 18 COVID-19 e-books for young children. The framework of analysis was based on the Grammar of Visual Design. Results indicate that the analysed images mostly assign children both roles of information receivers and active learners, while encouraging their engagement with what is represented. These interpersonal meanings largely align with the socio-cognitive perspective on young children's learning. The study could support teachers in the selection, design, and use of multimodal learning materials to promote children's visual literacy, especially in emergency conditions as those imposed by the COVID-19 pandemic.